2017
DOI: 10.5797/jnet.oa.2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Prasugrel with Endovascular Treatment for Unruptured Cerebral Aneurysm

Abstract: Objective: Recently, dual-antiplatelet therapy (DAPT) including clopidogrel (CLP) with endovascular treatment for unruptured cerebral aneurysm has been widely accepted. However, patients who are poor metabolizers of CLP (CLPPMs) are more frequent in East Asians than in Caucasians, and an adequate antiplatelet effect may not be achieved with a normal dose in such patients. Prasugrel, which is a novel thienopyridine antiplatelet drug that is less likely to be poorly metabolized than CLP, is used widely for percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“… 19) A recent Japanese study reported that prasugrel (loading dose: 20 mg, maintenance dose: 3.75 mg) was safe and effective in PMs of clopidogrel with endovascular therapy for unruptured cerebral aneurysms. 5) Internationally, several studies stated that low-dose prasugrel (loading dose: 20 mg, maintenance dose: 5 mg) was useful for the treatment of cerebral aneurysms. 7 , 20) A meta-analysis of these studies also demonstrated that low-dose prasugrel reduced thrombosis, and that it did not increase the incidence of hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported the safety and efficacy of prasugrel for clopidogrel resistance or thrombosis in patients undergoing neuroendovascular therapy. 5 7) Prasugrel resistance is rare, and the interval until its effects are observed is short. However, this drug has not been approved in the cerebrovascular field.…”
Section: Introductionmentioning
confidence: 99%